A longitudinal study of kinematic stride characteristics in maximal sprint running - Mattes, K.; Schaffert, N.; Habermann, N.; Mühlbach, T. (Journal of Human Sport & Exercise, 2014)
Purpose of the present study was to measure the kinematic stride characteristics of track-and-field-sprinters and jumpers in maximal sprint-running during different training periods (TP) of a double-periodisation (DP). 26 participants (7 females, age: 22.7 ± 5.7yrs, body mass: 60.1 ± 6.7kg, body height: 172.1 ± 4.4cm; 19 males, age: 20.9 ± 3.3yrs, body mass: 73.7 ± 6.5kg, body height: 182.3 ± 7.5cm) participated in flying 30-meter-sprints. Kinematic stride parameters (stride-velocity, stride-length, stride-frequency, contact-time, flight-time and stride-rhythm) were measured for every single stride with Optojump (Microgate S.r.L., Italy). The training data were collected via protocol. A variance analysis with repeated measures was calculated for 3 respectively 6 TPs as well as multiple regression functions for the stride-velocity. The longitudinal results showed significant values for the 6 TPs, however cyclic increase of maximal sprint-velocity (on average 0.42 ± 0.08m/s) with a DP that corresponded with the recorded training data. 3 TPs differed significantly in average stride-velocity, stride-length, stride-frequency and contact-time of the maximal sprint, but not in flight-time and stride-rhythm. Our findings suggest that kinematic stride characteristics depend on TP. A systematic training control to increase the sprint-speed must take into account these changes of the kinematic parameter during the training year.